Probabilistic Style of Thinking: the Essence of Concept and Properties - N I Arzumaniyan (Peoples' Friendship University of Russia (RUDN University), 2012)
In this article the specificity of the concept of «probabilistic style of thinking» is revealed, the argument that stochastics can be an effective way of formation of probabilistic style of thinking is given.